1998
DOI: 10.1016/s0009-9236(98)90182-5
|View full text |Cite
|
Sign up to set email alerts
|

Concentration-controlled zidovudine therapy*

Abstract: These data indicate that pharmacologic variability affects antiretroviral response. Furthermore, these findings provide a framework to characterize the pharmacologic determinants of effect and quantitate their contribution to the heterogeneity in clinical response to optimize therapeutic benefit.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...

Citation Types

5
43
1

Year Published

2000
2000
2016
2016

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 79 publications
(49 citation statements)
references
References 18 publications
5
43
1
Order By: Relevance
“…There are conflicting reports regarding the clinical relevance of the saturation of TMPK at clinical ZDV doses. Fletcher et al reported higher average amounts of cellular ZDV-TP and decreased variance (0.62 nM and 32% coefficient of variation [CV] versus 0.76 nM and 16% CV, respectively) when ZDV doses were adjusted to maintain a target plasma concentration (27), suggesting that variability between subjects in pharmacokinetics is important. However, the accumulation of ZDV-TP is further complicated, since phosphorylation is cell cycle dependent and the fraction of dividing cells may vary between HIV-infected individuals (48,49,59,86).…”
mentioning
confidence: 99%
“…There are conflicting reports regarding the clinical relevance of the saturation of TMPK at clinical ZDV doses. Fletcher et al reported higher average amounts of cellular ZDV-TP and decreased variance (0.62 nM and 32% coefficient of variation [CV] versus 0.76 nM and 16% CV, respectively) when ZDV doses were adjusted to maintain a target plasma concentration (27), suggesting that variability between subjects in pharmacokinetics is important. However, the accumulation of ZDV-TP is further complicated, since phosphorylation is cell cycle dependent and the fraction of dividing cells may vary between HIV-infected individuals (48,49,59,86).…”
mentioning
confidence: 99%
“…In the field of human immunodeficiency virus (HIV) therapeutics, substantial interpatient pharmacokinetic variability has been demonstrated and relationships between drug exposure and viral response have been observed for all three classes of antiretroviral agents (2, 6). Importantly, dose adjustment strategies designed to achieve target drug exposures and thereby reduce pharmacokinetic variability have resulted in improved virologic and immunologic outcomes (7,8).In addition to pharmacokinetics, another source of variability in outcomes is adherence. Therapeutic drug monitoring and pharmacokinetics have been discussed as approaches to monitor adherence but have not been systematically studied, partly because adherence has not been conceptually integrated into the basic pharmacologic dose-response paradigm.…”
mentioning
confidence: 99%
“…In the field of human immunodeficiency virus (HIV) therapeutics, substantial interpatient pharmacokinetic variability has been demonstrated and relationships between drug exposure and viral response have been observed for all three classes of antiretroviral agents (2, 6). Importantly, dose adjustment strategies designed to achieve target drug exposures and thereby reduce pharmacokinetic variability have resulted in improved virologic and immunologic outcomes (7,8).…”
mentioning
confidence: 99%
“…Studies conducted with HIV-infected populations have not established any relationship between ZDV or 3TC concentrations in plasma and the efficacy of these agents (19). On the other hand, a recent study showed a linear relationship between ZDV-TP intracellular concentrations and an increase in the percent change in CD4 ϩ cells from baseline in HIV-infected adults (5 Several approaches have been reported for the individual determination of ZDV-TP and 3TC-TP (6, 13, 15-18, 21, 22, 24). A recent approach was developed in which strong anionexchange-solid-phase extraction separated ZDV anabolites (ZDV-MP, ZDV-DP, and ZDV-TP), followed by enzyme digestion and quantification by radioimmunoassay (18).…”
mentioning
confidence: 99%